Sub-Saharan African Immigrant and Refugee Women’s Experiences of Mental Health and Supports in the Ottawa Region - Nguia Nyandja, Tiziane-Zeta (Université d'Ottawa | University of Ottawa, 2026)
Background. Literature on immigrant women shows they experience disproportionate mental health challenges linked to social determinants, raising public health concerns. Research highlights differences across racial and immigrant groups and emphasizes the need for intersectional services. However, few studies investigate sub-Saharan African women’s perspectives, including their experiences with mental health and barriers to accessing services. This study aims to provide insight into these critical issues. Approach. This study adopts a qualitative design using semi-structured interviews with 17 participants in Ontario from sub-Saharan African countries, including Benin, Cameroon, Congo, Djibouti, Gabon, Ghana, Ivory Coast, Nigeria, and Rwanda. Participants, aged 18 or older, immigrated to the National Capital Region at different times. Interviews averaged 60 minutes and were analyzed inductively using thematic analysis as outlined by Braun and Clarke (2006). This process involved data transcription, code generation, and the identification and refinement of themes. Study credibility was enhanced through rich descriptions, reflexivity regarding researcher bias, and member checking during the analysis process. Result. The findings indicate that sub-Saharan immigrant women’s mental health challenges are linked to their perceived success during resettlement. Although difficulties during resettlement shape the overall experience, mental health concerns are commonly influenced by life events such as childhood trauma, illness, postpartum experiences, or divorce, rather than resettlement itself. Participants expressed turning to culturally relevant forms of support, typically in the following order: prioritizing reliance on faith, seeking support from mothers, sisters and female friends, and occasionally designated cultural spaces or the wider community. The findings show that Western mental health services are accessed only as a last resort when other supports have not yielded relief. This study extends existing literature by highlighting the importance of alternative and culturally rooted support systems. Conclusion. This study explains limited use of formal mental health services, showing that limited awareness and pre-existing beliefs, competing settlement priorities, and reliance on alternative coping strategies reduces mental health prioritization. Formal care is usually sought only after individuals experience mental health challenges and find that alternative supports are not effective
Keywords: sub-Saharan African; African Women; Africa; African; Mental Health; Health Systems; Health Systems Reform; Mental Health; African Mental Health; Black Mental Health; Women's Health